Assessing creativity in a 'New Generation' architecture degree. (March 2016) - Onsman, Andrys
Abstract: The creative aspect of architecture remains a contentious issue, especially in terms of teaching and assessing at the tertiary level. Whereas creativity is generally acknowledged as an essential component of the design process, where and how it fits into the overall structure remains open to contestation. This paper develops an argument that identifying creativity as an alternate to expertise, allows teaching, learning and assessment to focus on process and product, especially in the Design Studio context. To normalize assessment a scoring rubric based on observed leaning outcomes that accommodate the development of expertise and creativity as aspects of both product and process generated.